Ultraendurance cycling in a hot environment: thirst, fluid consumption, and water balance - Armstrong, L. E.; Johnson, E. C.; McKenzie, A. L.; Ellis, L. A.; Williamson, K. H. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this field investigation was to identify and clarify factors that may be used by strength and conditioning professionals to help athletes drink adequately but not excessively during endurance exercise. A universal method to accomplish this goal does not exist because the components of water balance (i.e., sweat rate, fluid consumed) are different for each athlete and endurance events differ greatly. Twenty-six male cyclists (mean ± SD; age, 41 ± 8 years; height, 177 ± 7 cm; body mass, 81.85 ± 8.95 kg) completed a summer 164-km road cycling event in 7.0 ± 2.1 hours (range, 4.5-10.4 hours). Thirst ratings, fluid consumed, indices of hydration status, and body water balance (ingested fluid volume - [urine excreted + sweat loss]) were the primary outcome variables. Measurements were taken before the event, at designated aid stations on the course (52, 97, and 136 km), and at the finish line. Body water balance during exercise was not significantly correlated with exercise time on the course, height, body mass, or body mass index. Thirst ratings were not significantly correlated with any variable. We also observed a wide range of total sweat losses (4.9-12.7 L) and total fluid intakes (2.1-10.5 L) during this ultraendurance event. Therefore, we recommend that strength and conditioning professionals develop an individualized drinking plan for each athlete, by calculating sweat rate (milliliter per hour) on the basis of body mass change (in kilograms), during field simulations of competition.